Increased Serum Levels of S100A4 and S100A15 in Individuals Suffering from Hidradenitis Suppurativa - Aleksandra Batycka-Baran (MDPI AG, 2021)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease. Recently, some S100 proteins have been suggested to play an important role in the pathogenesis of chronic immune-mediated inflammatory diseases and they may constitute valuable biomarkers for these diseases’ diagnosis and monitoring. The objective of the current study was to investigate, for the first time, serum levels of S100A4 and S100A15 in individuals suffering from HS. Furthermore, we assessed the associations between S100A4 and S100A15 serum levels and the severity of disease, CRP serum concentration and some demographic and clinical data. Serum levels of S100A4 and S100A15 were evaluated with the commercially available ELISA kit according to the manufacturer’s instructions. The serum level of S100A4 in individuals with HS was significantly elevated as compared to controls, with the highest level found in the individuals in Hurley stage II. The S100A15 serum level was positively correlated with the CRP concentration and was associated with the severity of the disease. The serum level of S100A15 in the individuals in Hurley stage III was significantly elevated compared to that of the controls and the individuals with HS in Hurley stages I and II. S100A4 and S100A15 may be considered as new serum biomarkers for the monitoring of HS progression, and they may play a role in the pathogenesis of HS by promoting inflammatory process and fibrosis.